Article RETRACTED due to malpractice Physical Activity, Sleep Quality, Diet Quality and Menstrual Health in Female Adolescents - Siregar, Sarinah; Arvida Bar; Sholeha Rezekiyah; Witi Karwiti (Retos, 2026)
Background: Menstrual health problems are common among female adolescents and may negatively affect physical well-being, emotional stability, academic performance, and quality of life. Lifestyle-related factors such as physical activity, sleep quality, and diet quality have been increasingly recognized as important determinants of adolescent reproductive health. However, evidence regarding the combined influence of these factors on menstrual health among Indonesian adolescents remains limited. Objective: This study aimed to analyze the associations between physical activity level, sleep quality, diet quality, and menstrual health among female adolescents in Jambi City, Indonesia. Methods: A cross-sectional study was conducted among 312 female adolescents from SMA Negeri 6 and SMA Negeri 8 Jambi City, Indonesia. Data were collected using structured questionnaires assessing physical activity level, sleep quality, diet quality, stress level, screen time duration, and menstrual health status. Body mass index (BMI) was measured using standard anthropometric procedures and classified according to WHO adolescent BMI criteria. Bivariate analyses were performed using the Chi-square test, while multivariable logistic regression analysis was used to identify factors independently associated with menstrual health problems after adjustment for potential confounding variables, including age, age at menarche, BMI status, parental educational level, socioeconomic status, screen time duration, and stress level. Results: Nearly half of the respondents experienced menstrual health problems (46.8%). Low physical activity levels (63.0%), poor sleep quality (59.9%), and poor diet quality (58.2%) were associated with higher proportions of menstrual health problems (p <0.001). Multivariable logistic regression analysis demonstrated that poor sleep quality was the strongest predictor of menstrual health problems (AOR = 3.27; 95% CI = 1.89–5.66), followed by low physical activity (AOR = 2.84; 95% CI = 1.61–5.02), poor diet quality (AOR = 2.41; 95% CI = 1.37–4.23), and high stress level (AOR = 2.16; 95% CI = 1.23–3.78). Meanwhile, age, age at menarche, BMI status, screen time duration, parental educational level, and socioeconomic status were not significantly associated with menstrual health problems in the final model. Conclusion: Poor sleep quality, low physical activity, poor diet quality, and high stress levels were significantly associated with menstrual health problems among female adolescents. These findings highlight the importance of promoting healthy lifestyles and stress management strategies to improve adolescent reproductive health outcomes.